(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2022)
Lettuce (Lactuca sativa L.) is one of the most produced and consumed leafy vegetables in Brazil and worldwide. One of the main problems faced by producers is identifying the best time for weed control. The objective of this work was to evaluate the occurrence of programmed weeding on production components of the ‘Lucy Brown’ American lettuce. The experiment was carried out between March and May 2017, at the Federal University of Roraima, Cauamé Campus, located in Boa Vista, Roraima, Brazil. The experimental design adopted was in randomized blocks, with 6 treatments and 4 repetitions. The treatments consisted of: 100% weed control (100% WC), weed control 5 days after transplanting (WC 5 DAT), weed control 10 days after transplanting (WC 10 DAT), weed control 15 days after transplanting (WC 15 DAT), weed control 20 days after transplanting (WC 20 DAT) and 100% without weed control (100% WWC). The variables evaluated were: shoot height, stem height, stem diameter, number of leaves, leaf length, leaf width, root length, shoot fresh weight, total fresh weight, shoot dry weight and productivity. It is concluded that the ‘Lucy Brown’ lettuce must be weed-free after 5 days of transplanting the seedlings in order to avoid yield loss. The lack of weed control in the cultivation of ‘Lucy Brown’ lettuce causes a 71.88% decrease in its productivity.